Perception of local community and the willingness to pay to restore church forests: the case of Dera district, northwestern Ethiopia - Amare, D.; Mekuria, Wolde; Teklewold, T.; Belay, B.; Teshome, A.; Yitaferu, B.; Tessema, T.; Tegegn, B. (Informa UK Limited, 2016)
In the Ethiopian highlands, church forests have a substantial contribution to landscape restoration, and conservation of endangered indigenous tree species and biodiversity. However, the environmental and economic benefits of church forests are declining due to a combination of economic, environmental, and cultural factors. This study was conducted in Dera district, Ethiopia, to assess the perception of local communities on church forests and investigate the willingness of local communities to pay to manage and protect church forests. We used household survey and focus group discussion to gather data. Contingent valuation method and the Heckman two-step economic model were used to analyze data. Considerable proportion of the respondents (35%) mentioned several types of benefits that can be derived from church forests including fodder, fuelwood, tree seeds and seedlings, conservation of biodiversity, and improvement of the amount and distribution of rainfall. Respondents are also aware that sustainable management of church forests is essential to maintain or enhance the ecosystem services that can be obtained from existing church forests. Protection, fencing, plantation, and expansion of church forests were among the different management options suggested by the respondents. The majority (70%) of the communities are willing to contribute cash. On average, the farmers are willing to contribute ETB 32 (i.e., US$ 1.66 [Based on the exchange rate on 12 February 2014.]). Age, education, access to extension services, and amount of benefits derived from church forests were positively and significantly (p < 0.05) correlated with the willingness to pay. Providing training on forest management, putting a strong informal institution such as bylaws, and designing ways of moving from conservation to economic benefit are essential to restore and sustain church forests.